PRINSIP-PRINSIP SOPAN SANTUN DALAM BAHASA INGGRIS DAN BAHASA GORONTALO (ANALISIS KONTRASTIF) - Mulyani, Yayu; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Yayu MulyaniÂ¹Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dra. Theresia M.C. Lasut, M.HumÂ²Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Garryn Ch. Ranuntu, M.HumÂ³Â Â Â This research entitled â€œPoliteness Principles in English and Gorontalo Language: A Contrastive Analysisâ€ focuses on maxim related to politeness principles. The aims of this research are to identify, classify and analyze the polite utterances in English and Gorontalo Language according to politeness principles. In this research, the writer uses descriptive method. The English data were collected from pragmatic books, website, and some skripsi. In this research the writer uses Leechâ€™s theory to analyze the data and Lado theory in contrasting both languages to find out the differences and similarities. The polite principle in both languages that can be seen, such as requesting, commanding, and ordering, it is also shown by the acting of convincing what the speaker says. The result shows that there are six maxim of politeness principles and their function. Those are tact maxim, the genorisity maxim, the approbation maxim, the modesty maxim, the aggrement maxim, and the sympathy maxim. It is expected that this research will help students and readers in learning pragmatic, especially on politeness principles.Keywords: Pragmatic, Politeness, English, Gorontalo Language